Assessment of food microbiological indicators applied on poultry carcasses by culture combined MALDI-TOF MS identification and 16S rRNA amplicon sequencing. (September 2019) - Yu, Zhongjia; Peruzy, Maria Francesca; Dumolin, Charles; Joossens, Marie; Houf, Kurt
Abstract: Examination of the bacterial contamination on food products is still largely performed by standardized culture methods, though culture-independent methods are suggested as a more reliable approach. Knowledge of the diversity of bacteria isolated from food as well as the impact of the plate incubation conditions applied are still understudied. The impact of incubation at 7 °C and 30 °C on total aerobic bacterial count and diversity, and the performance of ISO methods generally applied in microbiological quality examination were assessed by culture combined MALDI-TOF MS identification and 16S rRNA amplicon sequencing. Examining breast skin of 16 chicken carcasses, no significant impact of the incubation temperature on the total aerobic bacteria level and diversity was detected, limiting the usefulness of additional psychrophilic examination. Bacteria phenotypically similar to Pseudomonas, were identified on selective CFC plates, and on MRS agar plates for lactic acid bacteria, Escherichia coli and Staphylococcus were commonly present. Application of 16S rRNA amplicon sequencing revealed a higher bacterial diversity, but the impact of the DNA extraction kit applied, and the detection of non-viable bacteria should be taken into account to interpret the final outcome. Highlights: Incubation at 30 °C and 7 °C have no significantly impact on TAB level. Relevance of psychrophilic bacteria detected at 7 °C incubation was limited. Currently applied selective medium overestimate the target bacteria. The application of 16S amplicon sequencing revealed a higher bacterial diversity. Interpretation of 16S amplicon sequencing can be affected by several factors.